1996
DOI: 10.1002/etc.5620151225
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of thiophene, benzothiophene, and benzofuran with eight different primary substrates

Abstract: Abstract-The aerobic biodegradation of thiophene, benzothiophene, and benzofuran was studied in microcosm experiments using groundwater microorganisms as inoculum. Benzofuran, a heterocyclic aromatic compound containing oxygen, was biodegraded as a sole source of carbon and energy measured by the disappearance of the compound, whereas two heterocyclic aromatic compounds containing sulphur (thiophene and benzothiophene) were not used as growth substrates. Thiophene was biodegraded with benzene, toluene, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Cometabolic reactions among aromatic compounds under aerobic conditions have been observed before. In previous studies [12,20], we observed that the condensed thiophenes likely were degraded cometabolically. But cometabolic reactions also have been observed among the monoaromatic compounds.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Cometabolic reactions among aromatic compounds under aerobic conditions have been observed before. In previous studies [12,20], we observed that the condensed thiophenes likely were degraded cometabolically. But cometabolic reactions also have been observed among the monoaromatic compounds.…”
Section: Discussionmentioning
confidence: 88%
“…In other experiments, using groundwater microorganisms from another creosote‐contaminated site and other groundwater microorganisms originating from the same aquifer as used in this study, it was observed that benzene may be used as growth substrate in the removal of thiophene [8,12,20]. It was also stated that the biodegradation of thiophene seemed to occur concomitantly with the biodegradation of benzene [12,20], but no strong conclusions were made at that time because of limitations in the data.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…S2c). Dyreborg et al [21] showed that although benzofuran could be used as a sole source of carbon and energy, its degradation could be enhanced in presence of a primary substrate. Degradation of benzofuran occurs by lateral dioxygenation which is catalyzed mainly by naphthalene dioxygenases.…”
Section: Biodegradation Of Different Nso Compounds By Various Enrichementioning
confidence: 99%
“…Studies on biodegradation of oxygen-containing heterocyclic compound benzofuran are very limited. Dyreborg et al [21] reported effective degradation of benzofuran as a single substrate as well as in the presence of other primary substrates such as naphthalene and 1-methylnaphthalene. However, there is no report on mechanism and identification of metabolites formed during benzofuran biodegradation.…”
Section: Introductionmentioning
confidence: 99%